Penerapan Model Terapi Aktivitas Kelompok Sebagai Alat Komunikasi tentang Stimulasi Persepsi Terhadap Peningkatan Harga Diri Lansia - Nuryanti, Lisna; Suriany Simamora, Rotua; Dedu, Baltasar Serilus Sanggu; Amir, Nurhidayah (Jurnal Kesehatan, 2023)
The elderly people experience biological, physical, psychological, and social changes. These changes bring impacts on many aspects of life, including health. The changes that occur in the elderly due to the aging process make them more vulnerable to experience physical and psychosocial problems. People could face many diseases when they are entering old age, such as degenerative diseases, decreased body function, increased brittle bones, reduced ability to carry out activities, reduced ability to maintain health, and maintain body balance as well as increased the risk of falling. This change in circumstances can affect self-evaluation, causing the elderly to lose self-esteem, feel worthless, and feel useless, leading to low self-esteem. Group occupational therapy is a therapy given to elderly people in groups by motivating them to remember past events or experiences. The aim of this research is to apply the group occupational therapy model as a communication tool related to cognitive stimulation to increase independence and respect from older people. This research uses a quantitative method with a before-after quasi-experimental design, without a control group, using a quota sampling technique and a simple random sampling method with a sample size of 15 respondents. The research results showed that after undergoing group occupational therapy, the self-esteem in the elderly is increased.